Kepastian Hukum Terkait Pengalihan Piutang (Cessie) dalam Praktik Kredit Pemilikan Rumah Ditinjau dari Kuh Perdata - Moh. Arpat Rasyid; Danil (PT PUSTAKA CENDEKIA GROUP, 2024)
The objectives of the study are: 1) To determine the legal certainty of the transfer of receivables (cession) without the consent and knowledge of the debtor in relation to the Civil Code, 2) To determine the procedure for the transfer of receivables (cession) of creditors to third parties as new creditors based on the Civil Code. This type of research is Normative research, namely a study that traces secondary materials, literature books, magazines, journals and laws and regulations as well as other legal documents to see the real conditions of the implementation of laws and regulations. In this study, Library Research was used, descriptive data analysis techniques, namely the author first describes the application of the material law that is applied. The conclusion of this study is 1) Cessie can be carried out based on a credit agreement made, as long as there is a clause regarding cession in the agreement. However, the clause must not conflict with Article 613 of the Civil Code, where cession must be with the knowledge or consent of the debtor in writing and is evidenced by the existence of a deed of transfer of receivables, either authentic or underhand. However, on the other hand, it can give rise to an opinion that the agreement is null and void because it does not comply with the objective requirements as stated in Article 1320 of the Civil Code, for the validity of an agreement four requirements are required, namely Agreement, Competence, Concerning a certain matter and A lawful cause. 2) The procedure for transferring receivables (cession) from a creditor to a third party as a new creditor based on the Civil Code can be carried out by transferring receivables (cession) to a third party according to the Civil Code. When a receivable is transferred, of course the creditor party also changes from the old creditor to the new creditor so that in terms of changing creditors, cession is also included in contract law, so it is also regulated by the third book of the Civil Code.